A “Lucan Effect” in the Commitment of Iranian Converts in Transit. The case of the Pentecostal Iranian Enclave in Istanbul - Johan Leman (Revue des Mondes Musulmans et de la Méditerranée)
Conversions are not uncommon among transit migrants towards the West. Christian churches, above all Pentecostalism, act as enclaves, also in Islamic countries. They offer a foothold and prospects for the future, in brief: hope. The newcomer grows towards a rebirth. Given that, fundamentally, both the transit migrant and the religious community are transnationally oriented, the convert ultimately discovers a new continuity between past, present and future. The more intensively he participates in the life in his Christian enclave, the more he approaches his initial objective (i.e. migration to the West).  It is a paradox like that illustrated by the parable in Luke 19:17. Hence our suggestion of a  “Lucan effect”, one that naturally calls for an empirically-based, rational explanation in a scientific article.